Some problems in lending to energy efficient projects and solutions - Sultonmurodov Bobir Bakhodirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Social and environmental development of the country is impossible without the active participation of commercial banks, credit support for both large businesses and small businesses, and private entrepreneurship. The process of developing the system of lending to energy-efficient projects affects the environmental interests of all entities operating in various market segments without exception. The banking system acts as an important market component and is a flexible tool for implementing macroeconomic goals. At the same time, the banking system is one of the main parts of the market infrastructure that connects all sectors of the economy and serves its sustainable social and environmental development.